An application and exploration of entrustable professional activities in Chinese orthopaedic postgraduate residents training: a pilot study - Qu, Rundong; Yang, Xu; Li, Ying; Gao, Fuqiang; Sun, Wei; Li, Zirong (Frontiers in Education, 2023)
Background: Through the standardization of residency training in certain Chinese medical education institutions, it was discovered that the current evaluation system falls short in accurately assessing residents' professional skills in clinical practice. Therefore, we developed the list of Entrustable Professional Activities (EPAs) in orthopaedic residency training to explore a new evaluation system. Methods: The process of constructing EPAs includes seven steps. 40 orthopaedic residents were randomly assigned to two groups (20 in each). The experimental group used the EPAs evaluation system while the control group employed the traditional Mini Clinical Exercise (Mini-CEX) system. Post-residency, theoretical and practical tests were conducted to measure training effectiveness. Additionally, a survey gauged teaching satisfaction, knowledge mastery, and course engagement in both groups. Results: The control group scored an average of 76.05 ± 10.58, while the experimental group achieved 83.30 ±8.69 (P<0.05) on the combined theoretical and practical test. Statistically significant differences were observed between the two groups concerning teaching satisfaction, knowledge mastery, and course engagement. Conclusions: The application of EPAs in orthopaedic residency training yielded higher theoretical and practical test scores compared to the traditional formative evaluation system. It also enhanced teaching satisfaction, knowledge mastery, and course engagement. The EPAs present a potential model for national orthopaedic residency training.